Modeling single event crosstalk speedup in nanometer technologies. Issue 5 (May 2015) - Sayil, Selahattin; Yuan, Li
Abstract With advances in CMOS technology, circuits become increasingly more sensitive to transient pulses caused by single event (SE) particles. In addition, coupling effects among interconnects can cause SE transients to spread electronically unrelated circuit paths which may increase the SE Susceptibility of CMOS circuits. The coupling effects among interconnects need to be considered in single event modeling and analysis of CMOS logic gates due to technology scaling effects that increase both SE vulnerability and crosstalk effects. This work reports on the signal speedup effects caused by SE crosstalk and then proposes a best-case delay estimation methodology for use in design automation tools for the first time to our knowledge. The SE coupling speedup expressions derived show very good results in comparison to HSPICE results. Results show an average error of about 8.42% for best-case delay while allowing for very fast analysis in comparison to HSPICE.